2009
DOI: 10.1590/s0037-86822009000500012
|View full text |Cite
|
Sign up to set email alerts
|

Padrão da infecção pelo HIV/AIDS em Manaus, Estado do Amazonas, no período de 1986 a 2000

Abstract: O objetivo deste estudo foi descrever a infecção pelo HIV em Manaus, Amazonas no período de 1986 a 2000. Estudo descritivo dos casos confirmados de HIV/Aids em adultos, registrados nos prontuários do Serviço de Referência Estadual, foi realizado. Para o delineamento da epidemiologia espacial e tendência histórica foram considerados os períodos: 1986-1990, 1991-1995 e 1996-2000. As variáveis comportamentais, sociais e clínicas foram analisadas por meio de estatística descritiva. Mapas temáticos apresentaram os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
5
0
5
Order By: Relevance
“…The increase in the number of individuals enrolled in the Santarém CTA/SAE in the study period confirms national epidemiological data related to the growth of the epidemic in the Northern region. 15 , 17 Grangeiro et al 10 (2011) stated that programmatic interventions such as the opening of CTA, development of the rapid HIV test, and changes in program management involving the decentralization of health care activities contributed to the increased reporting of cases in Northern Brazil. The mean incidence of AIDS was 25 cases/100,000 inhabitants in cities with CTA, compared with 17.5 cases/100,000 in other cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the number of individuals enrolled in the Santarém CTA/SAE in the study period confirms national epidemiological data related to the growth of the epidemic in the Northern region. 15 , 17 Grangeiro et al 10 (2011) stated that programmatic interventions such as the opening of CTA, development of the rapid HIV test, and changes in program management involving the decentralization of health care activities contributed to the increased reporting of cases in Northern Brazil. The mean incidence of AIDS was 25 cases/100,000 inhabitants in cities with CTA, compared with 17.5 cases/100,000 in other cities.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those found in other cities in the Northern region. Silva et al 15 (2009) evaluated 1,400 patients admitted with HIV/AIDS in Manaus, AM, Northern Brazil, between 1986 and 2000; of these, 50.8% had late diagnosis, with increased frequency of subjects admitted at later stages of the disease. Approximately 40.0% of HIV-positive individuals were admitted to reference health care units located in favela communities in Rio de Janeiro, RJ, Southeastern Brazil, in late stages.…”
Section: Discussionmentioning
confidence: 99%
“…Manaus has greater human genetic diversity because of their indigenous origin and sociocultural strong influence of migration from the Northeast region of Brazil since the 1800's when colonization occurred more intensely because of the business cycles of the rubber extractive exploratory projects, settlement of forest areas its transformation into an industrial area (Carneiro Filho, 1998). There is evidence that the HIV / AIDS in the city of Manaus evolved with different patterns of distribution and expansion, whose characteristics define its consolidation in the initially affected districts still in the emergency epidemic, spreading later to other spaces receptive City (Silva et al, 2009). In Manaus, it was found almost equal proportions of HIV-1 strains belonging to subtype B (51.6%) and F (48.4%), a finding that differs from previous results from studies conducted in urban areas of southeastern Brazil (Vicente et al, 2000).…”
Section: Hiv-1 Infection In the Brazilian Amazon Regionmentioning
confidence: 99%
“…This represents a contingent greater than 85% of all patients receiving ART, as well as concentrating data on incidence levels of AIDS, mortality rates and late diagnosis 2,5 . Studies on the HIV/AIDS epidemic in the region have indicated over time that the trend in the number of cases continues to increase principally in men, that tuberculosis (TB) is still the leading cause of death, and that respiratory failure is the main cause of hospital admission for these patients [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%